РROTECTION OF INFORMATION RIGHTS OF CITIZENS AS A DIRECTION OF LEGAL SCIENCE (Journal of actual problems of jurisprudence, 2020)
This article analyses the reasons for updating the protection of citizens ‘information rights in modernconditions. Informatization, and then digitalization, allows the state to collect all the necessary informationto ensure effective management and protect national and public security. However, informationsecurity issues of an individual person remain not fully protected from all sides: technological, technical,procedural, legal, etc. Based on the analysis of the structure of information rights, conclusions are drawnabout the need to rethink the content of the human right to information protection. Based on the studyof modern problems of information security of an individual, the author offers a number of recommendationsin the field of constitutional and information law. In particular, amendments to the classical theoryof human rights have been proposed. Namely, it is proposed to single out information rights, namely, thewhole complex of individual rights into a separate generation of rights. Such an approach, according tothe author, will ensure a comprehensive approach by the world community to solving problems of legalprotection, the development of international conventions and ensure control over their implementationat all levels.Key words: information, information rights, protection of information rights, information security,protection of individual rights.